Diet Intake Pattern and Nutritional Status of Rural Population in Bangladesh - Monoarul Haque, Md; Amirul Hassan, Md; Islam, Khaleda; Bhuiyan, Md Rijwan; Shahi, Md Shah Jalalur Rahman; Lipi, Rukhsana Parvin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Objective: The aim of this study is to explore the diet intake pattern and nutritional status of rural population in Bangladesh. Methods: A population based crosssectional study was conducted in three rural villages of Mohespur Upazilla, Jhenaidah district, Bangladesh. Total 200 samples were collected purposively to conduct this study. Data were collected through personal face to face interview by structured and semi-structured questionnaire from the respondents. Results: The mean (± SD) age of the respondents was 35±16.6 years where 64% were male. The monthly dietary intake pattern of the respondents shows that majority of the respondents take pulses, fish, meat, egg, milk and fruits 1 to 2 time per month. Majority (94.5%) of the respondents take cereals 2 to 3 times per day. In case of nutritional status, majorities (47%) have normal nutritional status where 30% are overweight, 15% are obese and 8% are suffering from underweight. Study also shows that there is no relation between gender and nutritional status of the respondents. Conclusion: Finally, this study indicates that the overall dietary intake pattern of rural population in Bangladesh is poor. Further study should be needed in a large scale to explore the real scenario of dietary pattern and nutritional status of rural population in Bangladesh. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21065